Theological Affinities Between the Fourth Gospel and the Book of Revelation - Köstenberger, Andreas J. (Perichoresis, 2024)
The focus of this study is on the exploration of theological affinities between the Fourth Gospel and Revelation. While I personally hold to the apostolic authorship of both writings by John, the son of Zebedee — admittedly a minority view in contemporary Johannine scholarship—the specific identity of the author will not be of primary concern here. Rather, my focus will be on the plausibility (or lack thereof) of common authorship, whether by the apostle or another writer. If it can be shown that the differences in outlook between the Fourth Gospel and Revelation may be accounted for by different subject matter, genres, and circumstances addressed, an important objection against the common authorship of the two documents will be removed.